Record-Breaking Slow Temperature Evolution of Spring Water During 2020 and Its Impacts on Spring Bloom in the Yellow Sea - Kim, Go-Un; Lee, Keunjong; Lee, Jaeik; Jeong, Jin-Yong; Lee, Meehye; Jang, Chan Joo; Ha, Kyung-Ja; Nam, SungHyun; Noh, Jae Hoon; Kim, Yong Sun (Frontiers in Marine Science, 2022)
Unprecedented retardation of spring water temperature rising during the 2020 pandemic year was identified in the Socheongcho Ocean Research Station within the northeastern basin of the Yellow Sea: an exceptionally high water temperature anomaly in March and a contrasted low-temperature anomaly in May. The slowest temperature evolution was principally caused by the significant increase in latent heat releases in April (117% higher than the climatology of 1982–2019). Strong northwesterly winds generated these exceptional heat fluxes associated with the dipole-like atmospheric circulation pattern over Siberia and the East Sea (Japan Sea). Besides, warm winter water facilitated the enhanced release of latent heat fluxes as a precondition. The oceanic heat redistribution partially supported the cold anomaly in the surface layer up to the middle of May through positive feedback between the low surface temperature and the active entrainment associated with tidal turbulent mixing. The resultant low temperature at the surface weakened the vertical stratification, both impeding the activation of phytoplankton’s photosynthesis albeit under the eutrophic surface layer, consequently resulting in the delayed and suppressed spring bloom during 2020. Since such extreme events are anticipated to occur more frequently under global warming, our results highlight the importance of continuously monitoring multi-disciplinary environmental conditions, climate extremes, and their impact on the Yellow Sea marine ecosystem.